Expert Opinion on the Therapeutic Use of the Fixed-Ratio Combination of Insulin Glargine 100 U/mL and Lixisenatide: a Central/Eastern European Perspective - Haluzík, Martin; Flekač, Milan; Lengyel, Csaba; Taybani, Zoltán; Guja, Cristian; Mihai, Bogdan-Mircea; Cerghizan, Anca; Martinka, Emil; Kovacs, Gabor; Kempler, Péter (Diabetes therapy, 2020)
The fixed-ratio combination (FRC) of a basal insulin and a GLP-1 receptor agonist (GLP-1 RA) has proven to be an effective therapeutic approach. However, physicians face numerous practical questions that cannot be answered by recently published trial results, current guidelines and summaries of product characteristics. In April 2019, a scientific meeting was held with the participation of nine experts from four Central and Eastern European countries to provide expert consensus on the optimal daily use of the insulin glargine and lixisenatide FRC (iGlarLixi). Topics included the positioning and initiation of iGlarLixi and the management of treatment. This paper summarizes the outcomes of the meeting.
Keywords: Fixed-ratio combination; Expert opinion; Insulin glargine and lixisenatide